Glass: Lapis Lazuli from the Kiln - Shortland, Andrew J. (Friends of the American Society of Overseas Research, 2021)
Today glass is all around us, it is familiar to us all in windows, vessels, spectacles, a myriad of uses. However, when glass was first made in the Late Bronze Age (LBA) around 1500 BCE it was very different.
Online Newsletter